SYSTEM DESIGN OF TRAFFIC LIGHTS AT SETTING TWO INTERSECTIONS FOUR PROCEDURES WITH THE INTERRUPTION TECHNIQUE - Syachrul Ahmad; Soebiyantoro, SSi, MMeng Soebiyantoro, SSi, MMeng (Jurnal Sistem Komputer, 2000)
conducting its activities, many researchers tried to apply with other electronic devicesmengapliasikannya with other electronic devices are not digital. Computers can bewidely used or common regulatory tools such as traffic lights, much used at thejunction of main roads or highways whose main function is to avoid congestion andtraffic accidents. Generally cause traffic jams that often occur due to traffic accidents,not vice versa. But in recent years, along with rapid economic development, thenmost of the roads in big cities in Indonesia are not able to accommodate passingvehicles, causing traffic jams. Accidents that may result in loss of life whencongestion occurs on the very small probability. But not so when the jam is located atthe intersection between two intersections, and there are railway crossing which isroad transport which have a higher priority of other land transport. Therefore it needsto make extra functions on the traffic control devices already exist. These additionalfunctions can be derived from the input signal-post guardhouse railway crossingwhen the signal is coming, then the traffic light on the jammed roads covering therailroads will be conditioned green. The duration of the green conditions can betailored to the needs, at least not block traffic to rail, so trains can pass safely. Thisalternative is at least able to reduce traffic accidents that cause loss of material andthe soul group should train with other ground transportation.